THE USE OF INTERACTIVE GAMES (EXERGAMES) IN THE PHYSICAL REHABILITATION OF CHILDREN WITH CEREBRAL PALSY: A COMPARATIVE STUDY WITH TRADITIONAL METHODS - Nahorniak, Mykhailo (European Journal of Interdisciplinary Issues, 2025)
One of the most common neurodevelopmental disorders in children is cerebral palsy, which is characterized by significant impairment of motor functions. Traditional rehabilitation methods are proven and effective, but they do not always motivate patients well. Interactive games based on virtual reality are actually a completely new concept in physical rehabilitation that can increase motivation as well as the functionality of therapy. Firstly, this study used the content analysis method, and secondly, the source of publications was databases such as PubMed, Scopus, Web of Science, Crossref, and Google Scholar. More than two hundred sources were found, and only 10-12 that met the inclusion criteria were selected for in-depth analysis. A comparative analysis of the results of treatment of children with cerebral palsy using exergames and traditional physical therapy was conducted. The correspondence of clinical scales, such as BOT-2 and DTVP-3, to interactive tasks, as well as the display of these similarities in the form of a correspondence matrix. Interactive games were found to have a good effect on the motor, visual-motor and cognitive functions of children with cerebral palsy. Exergaming had the same impact as adjusting difficulty levels, instant feedback, and incentive system on active patient participation and gradual improvement of skills. It was found that their functional goals of the application and test tasks, especially movement, dexterity and accuracy skills, were mutually consistent. Interactive games using VR technologies are a tool with great potential for the rehabilitation of children with cerebral palsy, especially when used as a supplement to traditional therapy. Not only do they provide therapeutic benefits, but they also ensure a high level of engagement and motivation. Further research with larger samples and longer interventions is needed to clinically prove the effectiveness of different types of exergames.